Hubungan Intensitas Penggunaan Media Sosial Dengan Eating Disorder Pada Remaja SMA - Siahaan, Sahat Elia Carlos; Tjahyadi, David (Metta : Jurnal Ilmu Multidisiplin, 2026)
Adolescence is a developmental stage highly susceptibel to psychososcial pressures, which contributes to an increased risk of eating disorders amidst the dominance of social media use. Although previous studies have shown contradictory result this, study aims to provide empirical clarification regarding the relationship between social media use intensity and eating disorder risk in adolescents. Utilizing a cross-sectional design, thos study involved 118 students at Regina Pacis Bogor High School selected through simple random sampling. Data were collected using the Social Networking Time Use Scale (SONTUS) and the Eating Attitude Test-26 (EAT-26) instruments, followed by Chi-square analysis. The findings indicated that the majority of respondents had a moderate instensity of social media use (58,5%) and were not at risk for eating disorders (84,7%). Statistical testing yielded a p-value of 0.721 (p>0,05), confirming the absence of significant contribution to adolescent mental healtth literature by demonstrating that social media use intensity is not the sole determinant in the development of eating disorders, rather othe multiaxial factors warrant further exploration.